Are universal banks better underwriters? Evidence from the last days of the Glass-Steagall Act - Dario Focarelli; David Marqués-Ibá\~nez; Alberto Franco Pozzolo (European Central Bank (ECB), 2011)
It has often been argued during the recent credit crisis that commercial banks' involvement in investment banking activities might have had an impact on the intensity of their underwriting standards. We turn to evidence from the period prior to the complete revocation of the Glass-Steagall Act in the United States and analyze whether investment banks or – section 20 subsidiaries of – commercial banks underwrote riskier securities. We compare actual defaults of these deals for an extensive sample of about 4,000 corporate debt securities underwritten during the period of the de facto softening of the Act's restrictions. Securities underwritten by commercial banks' subsidiaries have a higher probability of default than those underwritten by investment houses. This evidence is stronger in the case of ex-ante riskier and more competitive issues, and during the first years of bank securities' subsidiaries' entry into the market. Based on our results, it is not possible to reject that the repeal of the Glass-Steagall led to looser credit screening by broad (universal) banking companies trying to gain market share and/or to the lower initial ability of these banks to correctly evaluate default risk.
Keywords: G21; G24; N22; 330; default; Glass-Steagall Act; investment banking; securities underwriting